Application of novel nosocomial infection prevention and control combined with intestinal probiotics in children with hand, foot and mouth disease - Yuqiong Tao; Huibin Lu; Jinlian Huang; E Tang; Xiaoyan Xu; Jianhui Xie (Journal of the Pakistan Medical Association, 2025)
Objective:To explore the effect of novel nosocomial infection prevention and control combined with intestinal probiotics in children with hand, foot and mouth disease. Methods: The randomised case-control study was conducted at the Hunan Children’s Hospital, Changsha, China, from January 2022 to December 2023, and comprised of paediatric inpatients with hand, foot and mouth disease. The patients were randomised into control Group 1 receiving conventional treatment with basic nursing services, and intervention Group 2 receiving bacillus coagulans live tablets along with novel nosocomial infection prevention and control measures. The time of symptom resolution, fever resolution, length of hospital stay, clinical effect, serum inflammatory factors, immune function, incidence of adverse reactions, quality of life and parents’ satisfaction with nursing were noted and compared between the groups. Data was analysed using SPSS 22.0. Results: Of the 100 patients, 50(50%) were in Group 1; 25(50%) boys and 25(50%) girls with mean age 3.49±1.93 years. There were 50(50%) patients in Group 2; 26(52%) boys and 24(48%) girls with mean age 3.52±2.03 years (p>0.05). Compared to Group 1, patients in Group 2 had shorter time of symptom resolution, fever resolution, length of hospital stay, better total effective rate, lower frequency of adverse reactions and higher nursing satisfaction (p<0.05). After the intervention, improvements in serum inflammatory factors in Group 2 were more significant, the immune function indexes were higher, and the quality of life scores were better compared to Group 1 (p<0.05). Conclusion: Novel nosocomial infection prevention and control combined with intestinal probiotics could promote the therapeutic effect of the children, improve the immune function, and promote the quality of life of children with hand, foot and mouth disease. Keywords: Hand, foot and mouth disease, Nosocomial infection, Prevention and control, Intestinal probiotics, Immune function.